Distribution of velocities in a cross section using the logD method: application to a cross section of the Wainiha River - Milhous, Robert T., author; Colorado State University, publisher (Colorado State University. Libraries, 2018)
The logD method distributes velocities across a transect (cross section) uses the equation v = C√Sd log(α(d / k)). In the equation d is the depth at a location in the cross section, S is the slope, α is an empirical parameter, k is the absolute roughness height and C is a constant (32.61 for traditional English, and 18.00 for metric units). Typical value of α is 10.96 (based on theoretical considerations), and 4.70 (based on empirical measurements). The distribution of velocities in a cross section is used in the Physical Habitat Simulation System (PHABSIM) to calculate physical habitat for aquatic animals. The logD method is an effective method for calculation of the velocity distribution and helps reduce problems associated with the simulation of velocities at the edges of a channel. The method requires a consistence approach to the selection of the roughness heights. Roughness heights determined from measured velocities may not have a physical meaning but if roughness heights based on measured heights are used they must be used through out the cross section and not mixed with roughness heights determined from measured velocities.
Hydrology days 2018
AGU hydrology days 2018
2018 annual AGU hydrology days was held at Colorado State University on March 19 - March 21, 2018.